ESG, ENVIRONMENTAL COSTS, AND FIRM PERFORMANCE: THE MODERATING ROLE OF INDEPENDENT DIRECTORS - Mustafida, Nurul; Yosephina, Grace (Research In Management and Accounting (RIMA), 2025)
This study examines the influence of ESG scores and environmental costs on firm performance, as well as the moderating role of independent directors. Using secondary data and hypothesis testing, the findings show that ESG scores have a positive and significant effect on firm performance, supporting the Resource-Based View (RBV) framework that positions ESG as an intangible asset capable of enhancing operational efficiency, reputation, and legitimacy. Conversely, environmental costs exert a negative effect, indicating that in the short term they are perceived as financial burdens rather than strategic investments. The moderating role of independent directors is not supported, suggesting that their presence does not strengthen the relationship between ESG, environmental costs, and performance, although they still have a direct positive influence through accountability and conflict reduction. Theoretically, this study contributes to sustainability and governance literature by clarifying the dual role of ESG and environmental costs, while practically it highlights the need for efficient environmental cost management and institutional support to ensure that such expenditures generate long-term value. Limitations include reliance on secondary data, lack of industry-specific analysis, and the absence of board quality measures, offering directions for future research.